1999
DOI: 10.2331/fishsci.65.520
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Microsatellite Loci of <i>Clarias macrocephalus</i> and Their Application to Genetic Diversity Study

Abstract: Four microsatellite loci were identified for Clarias macrocephalus and the forward and reverse primers for each locus were designed according to their unique flanking regions. One locus, Cma-1 *, was monomorphic, three loci, Cma-2*, Cma-3 * and Cma-4*, were polymorphic having 5, 14 and 30 al leles per locus respectively. The polymorphic microsatellite loci were studied in four natural populations of C. macrocephalus collected from different locations in Thailand. Mean number of alleles per locus were 8.0, 8.7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
4
17
2
1
Order By: Relevance
“…This can be due to the extremely fast rates of repeat evolution that may differ among loci, but keeping the highly conservative flanking regions unchanged, as reported by Zardoya et al (1996) in cichlids and other Perciform fishes. The present study found GT and CA rich microsatellites abundant in G. curmuca which is in conformity with the published reports [45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…This can be due to the extremely fast rates of repeat evolution that may differ among loci, but keeping the highly conservative flanking regions unchanged, as reported by Zardoya et al (1996) in cichlids and other Perciform fishes. The present study found GT and CA rich microsatellites abundant in G. curmuca which is in conformity with the published reports [45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…The microsatellite flanking regions from siluriform species such as Pangasius hypophthalmus (Volckaert et al 1999), Clarias macrocephalus (Na-Nakorn et al 1999), and Clarias gariepinus (Galbusera et al 1996) were used to study the cross-species amplification of microsatellites in H. nigricollaris.…”
Section: Introductionmentioning
confidence: 99%
“…In H. brachysoma, a significant overall deficiency of heterozygotes was revealed in all populations, with the exception of some loci (Hbr Phy01 in Chalakkudy and Hbr Phy01 and Hbr Phy05 in Nethravathi). In Clarias macrocephalus, Na-Nakorn et al (1999) reported a deficiency of heterozygotes (H ob = 0.67; H ex = 0.76), but Watanabe et al (2001) and Usmani et al (2003) reported a significant excess of heterozygotes in other bagrid catfish, Pseudobagrus ichikawai (H ob = 0.54; H ex = 0.56) and Mystus nemurus (H ob = 0.499; H ex = 0.482). The deficiency of heterozygotes in allozymes and microsatellites in yellow catfish could be due to inbreeding, a situation caused by overexploitation leading to a decline of the species in the wild.…”
Section: Discussionmentioning
confidence: 97%
“…Stock identification of several species including catfishes has been carried out using allozymes (Shaklee et al 1990;Rognon et al 1998;Salini et al 2004;Haniffa et al 2007), RAPD (McCormack and Keegan 2000;Yan et al 2005;Chong et al 2000;Kovacs et al 2001;Nagarajan et al 2006), and microsatellite markers (Galbusera et al 1996;Na-Nakorn et al 1999;Volckaert et al 1999;Usmani et al 2001;Watanabe et al 2001, Saini et al 2010Abdul Muneer et al 2011a). In previous studies, we have identified these three markers in this yellow catfish species (Gopalakrishnan et al 2006a, b;Abdul Muneer et al 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation